Analyse spatiale et statistique de l’âge du Fer en France. L’exemple de la “ BaseFer ” - Christophe Batardy; Olivier Buchsenschutz; Katherine Gruel; Marc Levéry (Revue Archéologique du Centre de la France)
The development of Geographical Information Systems (GIS) allows information in archaeological databases to be georeferenced. It is thus possible to obtain distribution maps which can then be interpreted using statistical and spatial analyses. Maps and statistics highlight the state of research, the condition of sites, and moreover historical and cultural phenomena.Through a research programme on the Iron Age in France (Basefer), a global database was established for the entire country. This article puts forward some analyses of the general descriptive criteria represented in a corpus of 11000 sites (departments along the Mediterranean Sea coast are excluded from this test). The control and development of finer descriptors will be undertaken by an enlarged team, before the data are networked.